Hemorrhagic and thrombotic complications in patients with myeloproliferative diseases - Vignal, Carla Valladares; Lourenço, Dayse Maria; Noguti, Maria Aparecida Eiko; Chauffaille, Maria de Lourdes Ferrari; Kerbauy, José (São Paulo Medical Journal, 1997)
OBJECTIVE: To correlate the incidence of hemorrhage and thrombosis to bleeding time (BT) and platelet aggregation in 27 consecutive patients with myeloproliferative diseases (MPD). DESIGN: Retrospective study. SETTING: Public tertiary referral center. PATIENTS: Eighteen patients with chronic myelogenous leukemia (CML), 5 with polycytemia vera (PV), 2 with essential thrombocytemia (ET) and 2 with idiopathic myelofibrosis (MF). Duke’s BT and epinephrine-induced platelet aggregation were performed on the patients and on 10 healthy individuals. RESULTS: Eleven patients presented symptoms (41 %): 9 with hemorrhage (33%) and 5 with thrombosis (19%).There were less symptomatic patients in the CML group (28%) than in the other MPD (67%), without statistical significance (Fisher, p=0.06). Duke’s BT was longer in symptomatic patients (Mann-Whitney, p<0.05). Platelet aggregation was abnormal in 7 patients (26%) and 71% of them were symptomatic (Fisher, p = 0.07). CONCLUSIONS: The high incidence of bleeding and thrombosis in patients with MPD was related to prolonged BT, but not to platelet aggregation abnormalities.